Exploration of colonic looping patterns in undisturbed cadaveric specimens. Issue 7 (24th November 2020) - Lam, Jacob; Wilkinson, James; Brown, Jonathan; Spear, Michelle; Brassett, Cecilia
Abstract: Introduction: This study examines sex differences in the disposition of the sigmoid and transverse segments of the colon in undisturbed cadaveric abdomens and relates these findings to the anecdotal observation that colonoscopy is more challenging in females through the formation of tortuous bowel loops. Materials and Methods: One hundred and twenty two undisturbed cadaveric abdomens were inspected. Three distinct configuration grades were separately assigned to the sigmoid and transverse segments of the colon on the basis of the pattern of the bowel loops observed in situ. Pearson's chi‐squared test was used to analyze sex differences in bowel loop configuration and Spearman's rank correlation coefficient was calculated to identify co‐occurrence of configuration grades in the subjects. Results: For the transverse segment, females had higher configuration grades corresponding to longer bowel loops with greater redundancy, compared to males ( p = .000047). There was no sex difference in the sigmoid segment grade ( p = .21636). Sigmoid and transverse segment grades were highly correlated in the subjects (coefficient = 0.9994). Conclusion: Sex differences in the configuration grades of the sigmoid or transverse colonic segments may be a significant contributing factor to increased difficulty of colonoscopy in females.